Corona virus pandemic response among health workers in selected health facilities in Meru county - Kubai, Patrick (African Journal of Science, Technology and Social Sciences, 2023)
Abstract: Aims: The study aimed at determining the Level of knowledge, Preparedness and Response to Corona Virus Pandemic Outbreak among Health Care Workers in Meru County, Kenya. Study design: A cross-sectional study was adopted to conduct and determine Preparedness, Knowledge and Response of Health Care Workers (HCWs) to COVID-19 pandemic outbreak. Place and Duration of Study: Sample: Meru County, Igembe South Sub County Health Care Facilities between month of March and June 2020. Methodology: A cross-sectional study was conducted among HCWs to determine their Preparedness, Knowledge and Response to COVID - 19 Pandemic outbreak. The study population constituted of health care workers working in Igembe south in Meru County. Results: About 87 health care workers of mean age 34± 9 (SD) years with a minimum age of 19 years and maximum age of 70 years were recruited to take part in the study. Among the participants recruited in the study, 51 (58.6%) had bachelor’s degree, 30 (34.5%) participants had an ordinary diploma and 6 (6.9%) participants had a certificate level of professional qualification. Most 32 (36.8%) the participants were nurses. Other professional disciplines interviewed were Doctors, Clinicians, Nutritionists, Health Records Officers, Support staff, Social Workers among others. Significant number managers of the Health Care Facilities acknowledged receiving Ministry of Health Guidelines and Protocols on COVID-19 case management. Most (60; 69%) of the participants strongly disagreed that HCWs were trained on Case definition and management of Corona Virus Infections according to WHO guidelines i.e. Nurses (71; 81.6%), Clinical officers (62; 71.3%), Non-Core Health Care Workers (72; 82.8%) were well prepared, trained to handle cases of corona virus infections and associated emergencies. Response to COVID – 19 pandemic indicates that a significant number of (75; 86.2%) of participants strongly disagreed that Health Facilities were equipped with laboratories to test COVID -19, (70; 80.5%) of the participants strongly disagreed that PPEs were available and (70; 80.5%) of the participants strongly disagreed that Isolation and Consultation Rooms with dedicated clinicians are available. Overall a high proportion (73.6%) of the study participants strongly disagreed that they is good response to Corona Virus Pandemic out break interventions. Conclusion: Knowledge, Preparedness and Response levels to COVID -19 pandemic infection outbreak was at an average and there is need for continuous professional development (CPD) for HCWs to ensure adoption, maintenance of newly acquired appropriate practices during the COVID-19 pandemic to enhance preparedness and Response to the current and future outbreaks. This creates requisite capacity and skills among Health Care Professionals in their respective areas of practice considering that inadequate knowledge, preparedness and disjointed response which is not only an occupational hazard but a risk factor for poor delivery but also an occupational risk to the workers. Keywords: COVID -19, Corona Virus, Health Care Workers, Preparedness, Knowledge, Pandemic, Facilities, Response.